Post-laparoscopic cholecystectomy Mirizzi syndrome induced by polymeric surgical clips: a case report and review of the literature - Nagorni, Eleni-Aikaterini (J Med Case Rep, 2016)
BACKGROUND: Laparoscopic cholecystectomy is the gold standard treatment of gallbladder disease. Post-cholecystectomy syndrome is a severe postoperative complication which can be caused by multiple mechanisms and can present with multiple disorders. The wide use of laparoscopy induces the need to understand more clearly the presentation and pathophysiology of this syndrome. Post-cholecystectomy Mirizzi syndrome is one form of this syndrome and, according to literature, this is the first report that clearly describes it. CASE PRESENTATION: We describe the case of a 62-year-old Greek woman who underwent laparoscopic cholecystectomy because of gallstone disease. A few days after surgery, post-cholecystectomy syndrome gradually developed with mild bilirubin increase in association with epigastric pain, nausea, and vomiting. After performing ultrasound, magnetic resonance cholangiopancreatography, and endoscopic retrograde cholangiopancreatography, we conducted a second laparoscopic surgery to manage the obstruction, which was converted to open surgery because of the remaining inflammation from the post-endoscopic retrograde cholangiopancreatography acute pancreatitis. Four polymeric laparoscopic clips were removed because they were identified as the cause of her post-cholecystectomy syndrome. She had a quick recovery without further complications. CONCLUSIONS: Postoperative Mirizzi syndrome induced by the migration of polymer laparoscopic clips is a rare (only one case referring to polymeric clips has been published in the literature) but a well-identified complication of laparoscopic cholecystectomy which can confuse the diagnostic and therapeutic field requiring simultaneous immediate management.